CURRENT VIEWS ON THE STRUCTURAL ORGANIZATION OF THE RAT CEREBRAL CORTEX - Rybalka, Ya.V.; Yeroshenko, G.A.; Shevchenko, K.V.; Ryabushko, O.B.; Ulanovska-Tsyba, N.А.; Grygorenko, A.S.; Sokolenko, V.M. (World of Medicine and Biology, 2024)
In recent years, the structural organization and neurotransmitter nature of neurons in different parts of the rat cerebral cortex have provided the basis for further study and allowed the resulting experimental data to be extrapolated to humans in those aspects that are not related to the second signal system that is unique to humans. Advanced research methods have expanded the possibilities for research, so interest in studying the structural organization of the cerebral cortex has not abated to date. The cerebral cortex is the highest portion of the central nervous system. It is the youngest phylogenetically and the most complex part of the brain in terms of morphological and functional organization. It is the place of the highest analysis and synthesis of all the information entering the brain. It is the place where complex forms of behavior are integrated. The cerebral cortex is responsible for consciousness, thinking, memory, and “heuristic activity” (the ability to generalize and discover). A structural model based on systematic cortical variation captures the overall laminar structure of brain regions by dividing the cortical architectonic continuum into discrete categories (cortical types) that can be used to test hypotheses about cortical organization and function in different species, including humans. The architectonics data obtained from animal models provide an invaluable opportunity to reveal the complex interplay between structure and function in the mammalian brain. Extrapolation of these data from rodents to humans requires knowledge of the similarities and differences between species in anatomical features, and the factors that contribute to functional connectivity. Homologous functional networks are compared between species, and aspects such as global signal topography and the relationship between structural and functional connectivity are considered.
Keywords: cerebral cortex; rats; allocortex; olfactory sensory neurons; cortical amygdaloid nuclei; hippocampus; postrhinal cortex; isocortex